2010
DOI: 10.2353/ajpath.2010.090950
|View full text |Cite
|
Sign up to set email alerts
|

Novel Proteins Regulated by mTOR in Subependymal Giant Cell Astrocytomas of Patients with Tuberous Sclerosis Complex and New Therapeutic Implications

Abstract: Subependymal giant cell astrocytomas (SEGAs) are rare brain tumors associated with tuberous sclerosis complex (TSC), a disease caused by mutations in TSC1 or TSC2, resulting in enhancement of mammalian target of rapamycin (mTOR) activity, dysregulation of cell growth, and tumorigenesis. Signaling via mTOR plays a role in multifaceted genomic responses, but its effectors in the brain are largely unknown. Therefore, gene expression profiling on four SEGAs was performed with Affymetrix Human Genome arrays. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 59 publications
4
54
1
Order By: Relevance
“…The WTS results for both BEX1 and NPTX1 were confirmed by qRT-PCR in the xenografts from the study, and the induction of BEX1 by the drug combination was also confirmed in IM-sensitive GIST-T1 and IM-resistant GIST430 cell lines, providing cellular models for exploring this finding. Numerous reports in the literature implicate BEX1 and NPTX1 as tumor-suppressor genes or biomarkers in various cancers (33-35,37,38). Both genes have been implicated in connection with pro-apoptotic pathways in different cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The WTS results for both BEX1 and NPTX1 were confirmed by qRT-PCR in the xenografts from the study, and the induction of BEX1 by the drug combination was also confirmed in IM-sensitive GIST-T1 and IM-resistant GIST430 cell lines, providing cellular models for exploring this finding. Numerous reports in the literature implicate BEX1 and NPTX1 as tumor-suppressor genes or biomarkers in various cancers (33-35,37,38). Both genes have been implicated in connection with pro-apoptotic pathways in different cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Because effects of Cyr61 on dendrites were not previously reported, to additionally confirm that in case of Cyr61 knockdown our morphological criteria for dendrite selection are correct, we independently repeated experiment using either pSuper or Cyr61 shRNA pool transfection and quantified the number of MAP2-positive/Tau (PHF-1)-negative neurites. With such criteria we also showed that Cyr61 knockdown results in a significant decrease in the number of dendrites (pSuper/GFP (n ϭ 50), 22.58 Ϯ 0.72; Cyr61sh-mix (n ϭ 46), 16.09 Ϯ 0.61; p Ͻ 0.001; Mann-Whitney test). Because embryonic hippocampal cultures are mixtures of a large population of excitatory and a small population of inhibitory (glutamic acid decarboxylase (GAD67)-positive) neurons, we tested if knockdown of Cyr61 affects selectively one of them.…”
Section: Cyr61 Is Indispensable For Proper Dendritic Arbor Morphologymentioning
confidence: 96%
“…Recent phosphoproteomic studies identified several regulators of transcription and mRNA processing among mTOR substrates (43,44). Therefore, we decided to test whether the genes that encode mRNAs whose levels were previously shown to depend on mTOR activity (8,16,17) are involved in dendritic arbor development. To achieve this, we designed a minilibrary of shRNAs that target 46 such mRNAs (supplemental Table 1) using algorithms that proved to be accurate in over 66% of the cases in our previous studies (i.e.…”
Section: Overexpression Of S6k1 Is Not Sufficient To Induce Dendriticmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular changes that occur in SEGAs may be distinct from other TSC lesions and could account for their often relentless growth. In a recent study, gene array analysis in SEGAs identified numerous differentially expressed genes, in particular secreted frizzled-related protein 4, lactotransferrin, glycoprotein (transmembrane) nmb, annexin A1, Rho family GTPase 3, and S100 calcium binding protein a11 (Tyburczy et al, 2010). Another study using cDNA array and immunohistochemical analysis showed that epidermal growth factor (EGF), EGF receptor (EGFR), hepatocyte growth factor, c-Met, and vascular endothelial growth factor (VEGF), but not Flt-1, mRNA, and protein expression was upregulated in Tsc1 conditional knockout mouse brain, and these alterations closely predicted enhanced expression of these proteins in SEGAs (Parker et al, 2011;Fig.…”
Section: Introductionmentioning
confidence: 99%